Laparoscopic hemostasis for abdominal brunt massive hemorrhage due to endometriosis. Issue 2 (3rd November 2021) - Seki, Shiori; Ito, Kyoji; Takemura, Nobuyuki; Oikawa, Ryo; Koutake, Hikaru; Mihara, Fuminori; Yagi, Junko; Nakanishi, Misao; Tomio, Kensuke; Oishi, Hajime; Kokudo, Norihiro
Abstract: In the gynecological literature, a limited number of studies have reported intraperitoneal bleeding due to abdominal blunt trauma. In this report, we describe a rare case of massive intraabdominal hemorrhage from the uterine artery triggered by a fall injury without apparent abdominal bruising in the presence of severe endometriosis and a uterine fibroid. A 28‐year‐old woman who fell from a railway platform was transported to an emergency hospital. Although she did not sustain abdominal bruising and initially had no abdominal symptoms, she complained of gradually worsening abdominal pain. Abdominal CT identified intraabdominal massive hematoma, and emergency exploratory laparoscopy revealed active bleeding from the right uterine artery eroded by endometriosis, which was treated with laparoscopic electrocoagulation. The cause of the intraabdominal bleeding was associated with avulsion of the endometriosis adhesion between the right perimetrium and the right uterine artery due to inertial forces of the uterus during the fall injury. A uterine fibroid discovered during laparoscopy was suspected to strengthen the inertial forces of the uterus. In the case of hemoperitoneum after trauma, gynecological sources of bleeding must be kept in mind, especially for patients with a known history of fibroids or endometriosis.